2017
DOI: 10.1002/adsc.201700957
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium(II) Chloride‐Catalyzed Dehydrative C−P Coupling of Propargyl Alcohols with Diarylphosphine Oxides to Afford Allenylphosphine Oxides

Abstract: The cadmium(II) chloride-catalyzed dehydrative CÀP cross-coupling reaction of propargyl alcohols with diarylphosphine oxides is reported. Several propargyl alcohols including those bearing the sterically demanding tert-butyl group at the triple bond terminus can be used as good substrates in the reaction to produce the corresponding allenylphosphine oxides in good to high yields in acetonitrile at 100 8C. The reaction can also be easily scaled up to a gram-scale synthesis. A mechanism study indicates that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…Previous methods for the preparation of such compounds often suffered from some limitations such as poor substrate scope, complex or well‐defined ligands and the need for prefunctionalized starting materials. Recently, the groups of Gao, Yang, Liang, and Shen have independently reported the metal‐catalyzed direct dehydrative cross‐coupling reaction of unprotected propargylic alcohols and P(O)−H compounds, which provided a general, convenient, step‐ and atom‐economic procedure for accessing allenylphosphoryl compounds. In Gao's work, it was found that the use of 30 mol% of Cu(OTf) 2 as Lewis acid catalyst allowed the reaction to proceed smoothly at 100 °C with both unprotected terminal or internal secondary propargylic alcohols and disubstituted phosphine oxides, phosphinates or phosphonates (Scheme ).…”
Section: C(alkenyl)−p Bond Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous methods for the preparation of such compounds often suffered from some limitations such as poor substrate scope, complex or well‐defined ligands and the need for prefunctionalized starting materials. Recently, the groups of Gao, Yang, Liang, and Shen have independently reported the metal‐catalyzed direct dehydrative cross‐coupling reaction of unprotected propargylic alcohols and P(O)−H compounds, which provided a general, convenient, step‐ and atom‐economic procedure for accessing allenylphosphoryl compounds. In Gao's work, it was found that the use of 30 mol% of Cu(OTf) 2 as Lewis acid catalyst allowed the reaction to proceed smoothly at 100 °C with both unprotected terminal or internal secondary propargylic alcohols and disubstituted phosphine oxides, phosphinates or phosphonates (Scheme ).…”
Section: C(alkenyl)−p Bond Formationmentioning
confidence: 99%
“…The Shen group disclosed a CdCl 2 ‐catalyzed variant, in which the problem of compatibility of propargylic alcohols with sterically demanding substituents at the triple bond terminus was resolved (Scheme ). More importantly, the authors considered that the reaction proceeded through propargylic substitution of propargylic alcohols by Ar 2 P(O)H based on their O‐nucleophilicity instead of P‐nucleophilicity to generate phosphonite intermediate 81 followed by an intramolecular [2,3]‐sigmatropic rearrangement to produce the allenyl products.…”
Section: C(alkenyl)−p Bond Formationmentioning
confidence: 99%
“…Among them, the phosphorylation of alcohols with H-phosphine oxides has been successfully developed for the construction of C–P bonds since 2000 (Scheme , path C) . Subsequently, metal salts including Cu­(OTf) 2 , Pd­(acac) 2 , CdCl 2 , AgOTf, and Bi­(OTf) 3 exhibited excellent catalytic activities for the phosphorylation of allylic alcohols, propargylic alcohols, and tertiary aromatic alcohols. In 2017, Xie and Loh found the first example of C–P bond formation via a dehydrative cross-coupling reaction of C–OH/P–H from MBH (Morita–Baylis–Hillman) alcohols and phosphine oxides with high Z selectivity in the absence of catalysts, additives, and solvents . And they also achieved the dehydrative allylation of P–H species with allylic alcohols catalyzed by the strong Lewis acid B­(C 6 F 5 ) 3 .…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, an efficient method for the synthesis of allenyl organothiophosphates has not been disclosed yet. 13…”
Section: Introductionmentioning
confidence: 99%